Performance Analysis of Resilient Modulus and Fatigue Resistance of AC-BC Mixture with Full Extracted Asbuton and Reclaimed Asphalt Pavement (RAP) - Thopan Andhika Putra; Bambang Sugeng Subagio; Eri Susanto Hariyadi (Jurnal Teknik Sipil, 2022)
Abstract